Decentralization and local public goods getting the incentive right - Roumasset, James (1989)
The paper addresses the nature and locus of appropriate government control in the provision of collective services. It suggests some useful principles for determining organizational structures with the appropriate degree and form of decentralization, which is seen to be an important part of incentive compatibility. In the case of low-income housing, it cites the privatization of sites and services and the devolution of upgrading as two promising models of decentralization.
Includes bibliographical references (pages 11-13).
Keywords: Low-income housing; Privatization; Public goods